Prevalence of conceived violence against nurses at educational hospitals of Ilam, Iran, 2012 - Ali Ashraf Aivazi; Hamed Tavan (Elsevier, 2015)
Background and objectives: Health care staffs, all over the world, usually face harsh behavior. Violence in forms of verbal assault and physical action is experienced especially by hospital nurses; however, such violent behaviors are usually not reported, for some reasons. The aim of current study was to identify the workplace violence against nursing staff at educational hospitals of Ilam city (western Iran) in 2012. Materials and methods: A descriptive study was carried out during July to August 2012 at three educational hospitals of Ilam city. Data collection was done from 106 randomly selected nurses through a questionnaire on types of violence, their sources, and ways to cope with them. Data analysis was carried out through descriptive statistics & Chi-square test. Results: Totally, 43.84% of the participants had experienced and reported the violence, while the remaining 56.16%, despite being subjected to violence, did not report it. Out of all the studied people, 64.94% believed that reporting violence to officials would be useless. Considering the gender, 43% were male with reported violence rate of 53.57%, while the 57% population of females were reported a lower rate of 42.18% violence. Conclusion and recommendation: Since most the violent actions have not been reported, it is suggested to develop proper organizational infrastructures, educational programs on reporting such violent behaviors as well as their management. Furthermore, it is recommended to plan more comprehensive educational programs for patients and the community to reduce such undesired aggressive actions against the nurses and other staff at hospitals.